Nutritional Secondary Hyperparathyroidism in the Equines of Jammu Region - Bhardwaj, Rajinder Kumar; Kumar, Sudhir; Singh, Rajiv; Kumar, Ashok (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
A study was undertaken on 29 equines with a history of lameness, difficulty in mastication, reduced feed intake, and swelling of facial bones. Feeding history was recorded and clinical examination of all horses was performed. Radiographs of the head of some horses were taken. Blood samples were collected from 14 osteodystrophic and 6 healthy horses to estimate plasma levels of Ca, P, ALP, BUN, and creatinine. Urine samples were collected for a routine examination, sulkowitch test, urine calcium, and phosphorus estimation, and fractional urinary clearance of phosphorus was calculated. Mean values of P, ALP and UFCP was significantly higher in NSHP affected horse than healthy horses. Radiographs of the head revealed decreased bone density, loosened teeth in alveolar sockets, and increased osteoid thickening of maxillae and mandible bones. Young horses were more susceptible than older horses. All the animals were treated by supplementation of 40 gm of calcium carbonate orally for 2 months, resulting in the disappearance of lameness and returning animals to normal work.